Growth Response of Amaranthus gangeticus to Azotobacter chroococcum Isolated from Different Agroclimatic Zones of Karnataka - R. Surekha, R. Tejaswini, C.K. Suresh, C. Sandeep*, S.N. Rashmi, V. Sharmila, (Journal of Phytology, 2011)
In the present study Azotobacter chroococcum was isolated from various agro climatic zones of Karnataka. The effect of A. chroococcum isolates on seed germination of Amaranthus.gangeticus was studied and also the effect of A.chroococcum isolates on growth, biomass and nutrient content of Amaranthus gangeticus was studied under green house conditions. In seed germination studies the length of plumule and radicle was higher with inoculation of A. chroococcum isolates than uninoculated control plants. Treatments of A.chroococcum isolates from ten different zones of Karnataka were given to seedlings of Amaranthus gangeticus to study plant growth parameters such as plant height, number of leaves, number of branches, root length, shoot and root fresh and dry weight and nutrient uptake. Plants inoculated with Azotobacter isolates performed well when compared to uninoculated control plants. In Biochemical analysis chlorophyll content, nitrogen, phosphorous and potassium content was higher when compared to uninoculated control plants. The results of these experiments concluded that plants inoculated with Azotobacter isolates showed better growth response, biomass yield and nutrient content when compared with uninoculated control plants. Hence plants inoculated with A.chroococcum isolates were found to enhance the plant growth, biomass and nutrient content.